POLUSI UDARA DI RUAS JALAN PERKOTAAN - Gugun Gunawan (Jurnal Jalan-Jembatan, 2007)
Air pollution is mostly caused by motor vehicle in big cities which 70% air pollution is caused by motor vehicle activities, besides fuel and kind of vehicles which have influence on degree of air pollution are condition of topography, meteorogy, and , a chemical relation of each parameter. Results of monitoring air quality at road sides of big cities like Surakarta, Yogyakarta, Semarang, Surabaya, Denpasar (Bali), and Serang (Banten), with cities that through Pantura track, the air quality in some road sides more over and nearly the limit line of standar air quality ambient, as specially for pollutants oxide nitrogen (NOx), suspended particulate matter (SPM10) and hydrocarbon (HC). Evaluation with air pollution of standard index (ISPU) according to environment-regulation (Environmental Ministrial Decree) no. 45/1997. the condition is categorized Medium. When the air quality is no influence to human health or animals, but influence on sensitive-plant and aesthetic-value. Some strategies for air quality control in road-environment : a. Consideration and application policy and environment regulations become important steps to the whole rode-project cycle. b. participation of society in environment management as vehicle, owners road users, and social environment of roads. c. utilization fuel and vehicles that environmental-friendly d. application and arrangement of reduction technology air pollution and lansscape-plant. Keywords : Air Pollution, control,Urban, Community Role